Cholecalciferol vs. calcifediol supplementation on visceral adiposity in people with obesity: a real-world retrospective study - Chiurazzi, Martina; Di Lorenzo, Mariana; Lonardo, Maria Serena; Di Lauro, Mariastella; Onda, Carmela; Sozio, Concetta; Pacella, Daniela; Cacciapuoti, Nunzia; Guida, Bruna; Menale, Ciro (Frontiers in Nutrition, 2025)
IntroductionNowadays it is well known that obesity and vitamin D deficiency are closely linked. In this view, this study aimed to assess the effects of two different Vitamin D formulations, combined with a Mediterranean hypocaloric diet (MHD) on 25(OH)D concentration, weight loss and visceral adiposity in subjects with obesity and vitamin D insufficiency/deficiency.MethodsEighty-four patients with obesity were retrospectively selected and divided into three groups according to the type of treatment received: MHD alone (C group), MHD + cholecalciferol (D group), and MHD + calcifediol (N group). 25(OH)D concentration, anthropometric parameters, body composition and visceral adiposity indices (LAP, VAI, NVAI) were assessed at baseline and after 3 months.ResultsAll groups showed significant reductions in anthropometric parameters after 3 months. Notably, Group N achieved the greatest increase in serum 25(OH)D (+20 ng/mL), the highest weight loss (−7.8 Kg) and a significant improvement in LAP and NVAI. In addition, only N group showed an increased fat-free mass. Regression analysis confirmed a significant association between calcifediol treatment and LAP reduction, independent of BMI.DiscussionCalcifediol supplementation, combined with a MHD, is more effective than cholecalciferol in improving vitamin D status and reducing visceral adiposity in subjects with obesity. These findings support the recommended use of calcifediol supplementation in obesity-related vitamin D deficiency management.